2000
DOI: 10.1002/1096-9098(200009)75:1<42::aid-jso8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and treatment of postirradiation sarcoma of bone and soft tissue

Abstract: The prognosis for patients with peripheral resectable postirradiation sarcomas is good if a wide surgical margin can be achieved. This group of patients should be treated aggressively because they have a new cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 44 publications
2
92
0
1
Order By: Relevance
“…9,30 Our results suggest that this difference may be caused at least in part by the lower dose given to the patients who received orthovoltage radiation. Our study also suggested that the latency of RIS after megavoltage x-ray therapy was not only shorter than that after orthovoltage x-ray therapy but also was shorter than the latency after Cobalt-60 therapy.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 82%
See 3 more Smart Citations
“…9,30 Our results suggest that this difference may be caused at least in part by the lower dose given to the patients who received orthovoltage radiation. Our study also suggested that the latency of RIS after megavoltage x-ray therapy was not only shorter than that after orthovoltage x-ray therapy but also was shorter than the latency after Cobalt-60 therapy.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 82%
“…[18][19][20][21]29 In our study, we used the most common latency criteria of 3 to 4 years as reported by Arlen et al 21 The median latency in our series, 9.3 years, was consistent with data from other studies, in which the median latency ranges from 7.6 years to 22 years. [3][4][5][6][7][8][9][10][11]29 The shorter period of 7.6 years reported by Kuttesch et al 26 may be explained by the younger age of their patients. In addition, the administration of chemotherapy may shorten the interval between RT for the first cancer and the subsequent presentation of RIS.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…High-grade osteosarcoma, fibrosarcoma and malignant fibrous histiocytoma are the most common histologic types of radiationinduced sarcomas. The mean latency period ranges from 14 to 17 years (although some have occurred as soon as 3 years after RT), and the tumors are usually radioresistant [32,35]. RT-induced sarcomas were initially considered to have a grave prognosis compared with primary bone sarcoma, but subsequent studies have shown that aggressive treatment with chemotherapy and surgical resection improves the prognosis of RT-induced sarcomas, resulting in more than a 60% 5-year survival rate-approaching that of a primary bone sarcoma (50-80% 5-year survival rate) [33,35].…”
Section: Post-treatment Changesmentioning
confidence: 99%